Job creation and income generation in the cultural and creative industries: a case study of the shweshwe sewing industry - Mapuma, Aviwe Simbonge (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2019)
Worldwide, there has been a growing realisation of the importance of Cultural and Creative Industries as a driving force for employment creation, income generation and economic growth. Therefore, there is a need in South Africa to study and understand these industries setting, and business environment. Shweshwe is a unique local fabric produced by Da Gama Textiles in the Eastern Cape province of South Africa. This fabric is used by many micro-enterprises as an input to make clothes and other items for traditional cultural celebrations and ceremonies. This study is about the micro-enterprises who use South Africa made textiles (i.e. shweshwe textile) as business input. More specifically, it looks at employment creation and income generation opportunities of the micro-enterprises that use shweshwe textile as an input. These micro-enterprises and shweshwe production are being threatened by the rising influx of cheaper ready-made imported clothes that mimic the shweshwe designs and colours, in some cases, the logo as well. This study also plans to estimate the size and discover the attributes of the micro-enterprises that use shweshwe as an input in their businesses in South Africa, in order to estimate the impact of the counterfeit shweshwe imports on those micro-enterprises. This study adopted a mixed-methods approach-using a combination of both qualitative and quantitative data collection methods. Face-to-face interviews with questionnaires, were done with a total sample of 62 owners of the micro-enterprises that use shweshwe as input, in the Western Cape (Cape Town) and Eastern Cape (i.e. Makhanda and East London), South Africa. Self-administered questionnaires were emailed to 20 Jackson's Stores managers across the country. Lastly, face-to-face interviews were done with the key stakeholder-the representative of Cowie trading (the main shweshwe distributor) and Da Gama Textiles (the factory of shweshwe), during a field visit. The Qualitative data was analysed using thematic analysis, whereas the quantitative data was analysed using inferential and descriptive statistics. The results show, that the micro-enterprises that use shweshwe as input are a significant contributor in terms of employment creation and income generation in South Africa. They also reveal that there is a big number of micro-enterprises that use shweshwe as an input in SA. The findings showed an estimate of between 5077 and 6000 small businesses that are using shweshwe an input, which are associated with 10 900 to 12 900 jobs. It was also found out that there is a transformation in this industry, and that this sector is B-BEE compliant. There are also high levels of human capital in this industry. This is an important finding revealing that there is potential for future growth in this sector. Results also found that the majority micro-enterprise owners (80%) have no other source of income, meaning that they are highly reliant on their shweshwe sewing business income. Additionally, 85% of those business, shweshwe garments makes up half or more of their sewing business proceeds. This reveals that a decline in income caused by the import of ready-made clothes in "fake" shweshwe will have a negative impact on the micro-enterprises' ability to contribute to economic growth and job creation in this industry. To show the impact of the import of ready-made clothes in "fake" shweshwe on the micro-enterprises' ability to contribute to economic growth and job creation in this industry. In the questionnaires that were used to conduct face-to-face interviews with the micro-enterprises, respondents were asked to indicate whether they had other sources of income other than the income they generate from the shweshwe sewing business. They were further asked as follow up question to choose from a given list of possible options containing a range of percentages of their business income that comes from the work sewn with shweshwe. This question was asked in order to be able to see, if there were to be a decline in income caused by the import of ready-made clothes in "fake" shweshwe what impact it would have on the micro-enterprises that use shweshwe as an input. The theory of industrial organisation has adopted the view of that businesses operating in the formal sector are more efficient and productive than those in the informal sector (Lobato, 2010). The study found that the micro-enterprises that operate in the formal sector generate more turnover than the ones that operate in the informal sector. However, the theory was further tested by running OLS regression, the results showed that operating in the informal sector does not affect turnover when other variables are controlled for, however, that it does affect job creation. In closing, this thesis provides suggestions on how to support, and protect the micro-enterprises that use shweshwe as an input, in order to enhance this industry's potential also to ensure its continuous contribution in terms of employment creation and income generation in South Africa.
Keywords: Textile industry -- South Africa -- Eastern Cape; Clothing trade -- South Africa -- Eastern Cape; Sewing -- South Africa -- Eastern Cape; Job creation -- South Africa -- Eastern Cape; Textile manufacturers -- South Africa -- Eastern Cape; Textile fabrics; Income -- South Africa -- Eastern Cape